Potential and requirements of IT for ambient assisted living technologies: results of a Delphi studiy - Spitalewsky, Katharina; Rochon, Justine; Ganzinger, Matthias; Knaup-Gregori, Petra (Methods of information in medicine, 2013)
Objectives: Ambient Assisted Living (AAL) technologies are developed to enable elderly to live independently and safely. Innovative information technology (IT) can interconnect personal devices and offer suitable user interfaces. Often dedicated solutions are developed for particular projects. The aim of our research was to identify major IT challenges for AAL to enable generic and sustainable solutions. Methods: Delphi Survey. An online questionnaire was sent to 1800 members of the German Innovation Partnership AAL. The first round was qualitative to collect statements. Statements were reduced to items by qualitative content analysis. Items were assessed in the following two rounds by a 5-point Likert-scale. Quantitative analyses for second and third round: descriptive statistics, factor analysis and ANOVA. Results: Respondents: 81 in first, 173 in second and 70 in third round. All items got a rather high assessment. Medical issues were rated as having a very high potential. Items related to user-friendliness were regarded as most important requirements. Common requirements to all AAL-solutions are reliability, robustness, availability, data security, data privacy, legal issues, ethical requirements, easy configuration. The complete list of requirements can be used as framework for customizing future AAL projects. Conclusions: A wide variety of IT issues have been assessed important for AAL. The extensive list of requirements makes obvious that it is not efficient to develop dedicated solutions for individual projects but to provide generic methods and reusable components. Experiences and results from medical informatics research can be used to advance AAL solutions (e.g. eHealth and knowledge-based approaches).